2015
DOI: 10.1093/ejcts/ezu532
|View full text |Cite
|
Sign up to set email alerts
|

Dilated left atrium as a predictor of late outcome after pulmonary vein isolation concomitant with aortic valve replacement and/or coronary artery bypass grafting

Abstract: In patients with paroxysmal AF related to aortic valve disease and/or coronary artery disease, a dilated left atrium (≥45 mm) was associated with inferior AF- and event-free survival after PVI, accompanied by persistent abnormalities in cardiac and haemodynamic function. These findings may assist patient selection for PVI during AVR and/or CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“… 1345 The application of bipolar RF clamps to perform PVI has shown variable 50%-89% 1-year success superior to AAD alone in patients with paroxysmal and persistent AF. 1346 , 1347 , 1348 , 1349 , 1350 A recent meta-analysis of 16 RCTs of surgical ablation and concomitant operations evaluated predominantly mitral operations, but included both AVR and CABG operations. 1333 There were no significant differences in mortality, stroke, or pacemaker requirement between surgical ablation compared with no ablation; however, the surgical ablation groups demonstrated superior 1-year freedom from AF in AVR and AVR+CABG.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“… 1345 The application of bipolar RF clamps to perform PVI has shown variable 50%-89% 1-year success superior to AAD alone in patients with paroxysmal and persistent AF. 1346 , 1347 , 1348 , 1349 , 1350 A recent meta-analysis of 16 RCTs of surgical ablation and concomitant operations evaluated predominantly mitral operations, but included both AVR and CABG operations. 1333 There were no significant differences in mortality, stroke, or pacemaker requirement between surgical ablation compared with no ablation; however, the surgical ablation groups demonstrated superior 1-year freedom from AF in AVR and AVR+CABG.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…The literature also reports different ablative sources (e.g., radiofrequency and cryoablation) and different surgical techniques (e.g., epicardial versus endocardial ablation). Some studies have also noted that duration of AF and LA size are important predictors of ablation failure [177,179].…”
Section: Surgical Management Of Atrial Fibrillation In the Context Ofmentioning
confidence: 99%
“…Of the 24 included studies, 12 of them were dedicated to reporting the surgical treatment of AF in patients undergoing CABG (16, 20, 2233). Data about CABG patients were extracted from the subgroup analysis of the remaining 12 studies, which were principally reported concomitant cardiac surgery outcomes (3446). The full Cox-Maze lesion set was used only in 4 (17%) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were included to report the outcomes of pulmonary vein isolation (PVI) for the treatment of atrial fibrillation in this patient population. Subgroup analysis was used to extract data in 1 of 6 papers (46).…”
Section: Resultsmentioning
confidence: 99%